2010
DOI: 10.1007/s11136-010-9720-7
|View full text |Cite
|
Sign up to set email alerts
|

Development of sense of coherence in adulthood: a person-centered approach. The population-based HeSSup cohort study

Abstract: This analysis shows continuous increase in the level of SOC over time to be common in adulthood, irrespective of age. High SOC, rather than higher age, seems to determine a stable development of the SOC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
61
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(76 citation statements)
references
References 39 publications
(72 reference statements)
7
61
0
4
Order By: Relevance
“…The SOC seems to be relatively stable over time, but not as stable as initially assumed (Eriksson & Lindström, 2011). Research findings show that the SOC develops over the entire lifespan, in other words it increases with age (Feldt et al, 2007(Feldt et al, , 2011Nilsson, Leppert, Simonsson, & Starrin, 2010). In the HeSSup study among 18.525 Finns, the SOC seemed to increase with age in terms of being more stable among subjects aged 30 and over (stability coefficient 0.81) than among younger adults (0.70) (Feldt et al, 2007).…”
Section: How the Soc Develops In The Life Coursementioning
confidence: 97%
“…The SOC seems to be relatively stable over time, but not as stable as initially assumed (Eriksson & Lindström, 2011). Research findings show that the SOC develops over the entire lifespan, in other words it increases with age (Feldt et al, 2007(Feldt et al, , 2011Nilsson, Leppert, Simonsson, & Starrin, 2010). In the HeSSup study among 18.525 Finns, the SOC seemed to increase with age in terms of being more stable among subjects aged 30 and over (stability coefficient 0.81) than among younger adults (0.70) (Feldt et al, 2007).…”
Section: How the Soc Develops In The Life Coursementioning
confidence: 97%
“…Both within adult (Feldt et al, 2011;Eriksson and Lindström, 2005) and adolescent (Buddeberg-Fischer et al, 2001;Nilsson et al, 2003) samples greater stability of SOC has been found amongst those with an initially strong SOC compared to those that started from a lower base. Some very valuable longitudinal large scale studies in adult populations have significantly contributed to our current understanding of this matter (Feldt et al, 2011;Volanen et al, 2007). However, despite this evidence, understanding stability and change requires a careful consideration of life events occurring during the period of analysis.…”
Section: Salutogenesis and Explanationmentioning
confidence: 93%
“…He suggested that SOC is dynamic, which means that it could change over an individual's life span. Specifically, he proposed two hypotheses, referred by Feldt et al (2011) as the age hypothesis and the level hypothesis. According to the age hypothesis, SOC is unstable and tentative until the third decade of life.…”
Section: Salutogenesis and Explanationmentioning
confidence: 99%
“…The significant influence of SOC on employee health in the work context has been well established (Vogt, Jenny & Bauer, 2013) and widely explored as reflective of one's psychological well-being and coping ability (Austin & Cilliers, 2011;Feldt et al, 2011). SOC was originated by Antonovsky (1979) as the fundamental construct in his salutogenic theory.…”
Section: Sense Of Coherencementioning
confidence: 99%
“…Salutogenic theory is a health-oriented theory about the SOC construct and is based on the notion that people's orientation to the world provides them with the strength and capacity to resist distress and mental ill health in the midst of challenging circumstances (Liukkonen et al, 2010). Salutogenic theory thus focuses on describing SOC as an orientation to life which facilitates coping and thriving in difficult circumstances (Feldt et al, 2011). Whereas well-being constructs such as happiness and SWB denote a reflective perspective of ones well-being, SOC represents a perspective that provides the individual with agency and active control in responding to environmental stressors.…”
Section: Sense Of Coherencementioning
confidence: 99%